IMF Committee on Balance of Payments Statistics : Annual Report 2015. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2016)
The 2015 Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) provides an overview of recent trends in global balance of payments and international investment position (IIP) statistics, summarizes the Committee's work program during 2015, and presents the work program of the Committee in the coming year.